IS “TWILIGHT” A HOME RUN BOOK? - Kyung Sook Cho (Indonesian JELT, 2010)
Thirty-two young adults, students of English as a Foreign Language, were asked to read a portion of “Twilight”, a book that has become extremely popular among teenagers and young women world-wide. Even though the group as a whole were not involved pleasure readers in English, reading just a small part of Twilight stimulated the students enormously. They wanted to read more from the same series, and more in general, Multivariate analysis confirmed that interest in reading the book was the major predictor in students' desire to read more from the Twilight series.Keywords:   English as a foreign languge, twilight, multivariate analysis.